Depression Detection System: A Systematic Review - P. Acharya, Jiger; S.Shah, Milind (Journal of Neonatal Surgery, 2025)
Depression is mood disorders which result in severe disabling conditions affect person’s ability to cope with routine life challenges. It may occur when person remain more than two weeks in negative state of mind continuously. Depending on severity depression is classified as mild, moderate and severe. The World health organization (WHO) list depression as major cause of suffering and disability worldwide more than 350 million people are affected and predict to be leading cause in 2020[1],[2]. Psychosocial and clinical treatments are available but persons have tendency to conceal it. Depression has observable behavioral symptoms related to affective and psychomotor domains which can be identified by human or machine. Classical approaches concerned to person’s behavioral analysis and family observations during clinical interviews which are effective if it can be explicitly defined and precisely assessed while automatic system perform the said task effectively and open a new era for health care domain.